Pengaruh Terapi Akupunktur Terhadap Glikohemoglobin Darah pada Pasien Obesitas di Pos Kesehatan Lansia Surakarta - Sumanto Sumanto; Joko Tri Haryanto (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Abstract Background: Obesity and overweight are often associated with the risk of type 2 diabetes mellitus. The impact of obesity and overweight is not only one of the factors causing dysfunction of organs such as the heart, blood vessels, nerves and senses of sight and touch to peripheral nerve damage, but also causes a decrease in the quality of human resources, caused by physical and mental disorders to increase health costs. The incidence of type 2 diabetes mellitus in Indonesia is 10.6 million between the ages of 20 - 79 years out of a total Indonesian population aged 20 - 75 years of 175.1 million. Based on the results of the International Diabetes Federation survey, 2019, Indonesia is ranked 7th in the world with the highest number of diabetes mellitus patients. Objectives: HbA1C examination is an examination that aims to predict the onset of DM disease by knowing the degree of blood glucose metabolism during the last 2-3 months. The International Expert Committee determined the importance of HbA1C examination in screening DM disease diagnosis (American Diabetic Association, 2014). Methods: This study used a quasi-experimental approach with a control group. This quasi-experimental research is a study that manipulates acupuncture therapy treatment in obese and overweight patients. This study involved 1 group, namely the treatment group to find the cause and effect relationship, as well as the amount of contribution between these relationships. Results: Bivariate analysis of data using paired t test on blood glucose levels of overweight patients amounted to 0.655 with a probability significance level (sig.) p of 0.524. This shows that the sig. p value of 0.524> p 0.05, meaning that acupuncture action in overweight patients has no effect on blood glucose levels. Conclusion: Analysis of Hb.A1c data in overweight patients showed 9.167 and a probability significance value of p=0.000. This shows that acupuncture action in overweight patients has an effect on Hb.A1c levels. Keywords: Acupuncture, Uric Acid, Elderly